La trazabilidad de los textos filosóficos y sociopolíticos en la traducción: del origen al mercado editorial. - Enríquez-Aranda, Mercedes (Comares, 2024)
This book presents a comprehensive overview of the professional practice of translating philosophical and sociopolitical texts in Spain today, with special, but not exclusive, interest in the English-Spanish language combination. The translation of books in the philosophical and sociopolitical fields is professionally framed in Spain within editorial translation. Although this translation activity represents an important part of editorial production in the current Spanish market, until now little attention has been paid to its theoretical study, to its study in relation to the professional demands and competences that define the task of the translator, and to its study from a teaching methodological perspective. This is, therefore, a pioneering reference work for researchers, professional translators, teachers and students especially interested in translation for the publishing world in these fields. It is also structured in an innovative way that is consistent with the need for knowledge transfer in a double flow between university and business. The book begins with an identification of the origin of the translation of philosophical and sociopolitical texts and then traces the path that these translations follow until their publication in the publishing market, also addressing the analysis of the specific professional skills that allow the translator of these texts to carry out a wide range of tasks related not only to the cultural and ideological load that must be calibrated, but also to a large extent to the context in which their activity is inserted and to the participants in the translation process.
Autorización sólo para acceso cerrado.
Keywords: Traducción; Filosofía - Traducciones; Estudios de traducción; Traducción e ideología; Traducción y cultura; Traducción de textos filosóficos